2020
DOI: 10.3389/fonc.2020.602661
|View full text |Cite
|
Sign up to set email alerts
|

Role of Autophagy in the Microenvironment of Oral Squamous Cell Carcinoma

Abstract: Oral squamous cell carcinoma, the most common type of oral cancer, affects more than 275,000 people per year worldwide. Oral squamous cell carcinoma is very aggressive, as most patients die after 3 to 5 years post-diagnosis. The initiation and progression of oral squamous cell carcinoma are multifactorial: smoking, alcohol consumption, and human papilloma virus infection are among the causes that promote its development. Although oral squamous cell carcinoma involves abnormal growth and migration of oral epith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 105 publications
0
16
0
Order By: Relevance
“…Autophagy-related genes (ARGs) are molecules that participate in autophagy. In recent studies, many researchers deemed that autophagy is an important process in ORCA [ 6 8 ]. Most of the molecular mechanisms which are involved in autophagy regulation deeply participate in signaling pathways that assumed significant roles in ORCA control [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Autophagy-related genes (ARGs) are molecules that participate in autophagy. In recent studies, many researchers deemed that autophagy is an important process in ORCA [ 6 8 ]. Most of the molecular mechanisms which are involved in autophagy regulation deeply participate in signaling pathways that assumed significant roles in ORCA control [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although multiple treatment options are available, such as surgery, radiotherapy, and chemotherapy, the clinical heterogeneity and lack of early detection of HNSC cause the 5-year survival rate to be less than 50% [ 9 ]. Studies have shown that autophagy and ferroptosis are fundamental cellular events, which have been found to affect a variety of characteristics of HNSC, including proliferation, migration, and drug resistance [ 10 , 11 , 12 , 13 ]. While autophagy occurred in tumor cells, the formation of double-membrane autophagic vesicles could be observed by using a transmission electron microscope (TEM) [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Abnormal autophagy has been associated with cancer and other diseases [ 58 ]. Several studies have demonstrated that autophagy helps cancer cells overcome nutritional limitations and promotes cell growth [ 59 , 60 , 61 ]. Therefore, the inhibition of autophagy in cancer cells appears to be an appropriate treatment strategy.…”
Section: Discussionmentioning
confidence: 99%